Cognitive and metacognitive strategies in reading scientific texts among ESL science undergraduates / Samsiah Abdul Hamid - Abdul Hamid, Samsiah (2012)
The present study employed both quantitative and qualitative data collection techniques to investigate the pattern of strategy use of high and low English proficiency science learners and the impact of metacognition, English proficiency and scientific prior knowledge on strategy use and reading comprehension of two scientific texts. Research instruments used include Metacognitive Awareness inventory (Schraw and Dennison, 1994), an 80-item Scientific Text Academic Reading Strategy (STARS) inventory, Scientific Prior Knowledge inventory, two scientific texts of different syntactic difficulty and topic familiarity, and three different measures of reading comprehension of scientific texts. Think-aloud methods and retrospective interviews were utilized to collect the qualitative data of five case studies. The major findings from the quantitative study indicate that L2 proficiency contributes in the range of 5.2% to 24.3% to the variance in second language reading comprehension of scientific texts, higher cognitive strategies, in particular summarizing and analyzing visual diagrams, contribute another 11%, and the knowledge of scientific terminology contributes some 1.5% to 2.2%. In sum, the findings reveal that the contribution of L2 proficiency to the reading comprehension of scientific texts increases with the increase of readers‘ proficiency and texts difficulty. The evidence gathered from the quantitative and qualitative data shows that L2 proficiency remains the pre-requisite for reading and understanding L2 scientific texts but it is not the ultimate predictor of good L2 readers of the text. iii One surprising finding is the role of metacognitive awareness as a predictor to the reading comprehension of a scientific text. It was found that high metacognitive awareness possessed by ESL readers could be stymied by their low L2 proficiency and lack of independent reading practice, thus render it ineffective. The data of this study also indicated that in reading scientific texts, scientific prior knowledge, as opposed to general prior knowledge, is crucial to reading comprehension and scientific prior knowledge is not vigorously accessed when it exists in abundance but when it does not. Finally the thesis discusses the theoretical and pedagogical significance of the study and provides suggestions for future research.